The Pillars of Trading Insiders who are Familiar with the Internal Information of the Company Listed on the Stock market : A Comparative Study - Ahmed, Suha; Falhi, Haifa (Journal of Legal Sciences, 2023)
Although the obligation to disclose is one of the factors that greatly affect the success of the stock market and achieve the stability of transactions, this obligation should not be understood in absolute terms, as there are secrets for the company and for market participants that should not be disclosed in a way that harms them and thus negatively affects the market. Accordingly, this study deals with a very important topic, which is the legal regulation of the internal information of the company listed in the stock market, as the exploitation of this information has a positive or negative impact on the price of the security issued by the company. that It violates the principle of equality among investors, in addition to creating imbalances with regard to the protection.